Important lack of difference in tacrolimus and mycophenolic acid pharmacokinetics between Aboriginal and Caucasian kidney transplant recipients. Issue 9 (29th June 2022) - Barraclough, Katherine A.; Metz, David; Staatz, Christine E.; Gorham, Gillian; Carroll, Robert; Majoni, Sandawana William; Cherian, Sajiv; Swaminathan, Ramyasuda; Holford, Nick
Abstract: Aim: To examine whether differences in tacrolimus and mycophenolic acid (MPA) pharmacokinetics contribute to the poorer kidney transplant outcomes experienced by Aboriginal Australians. Methods: Concentration‐time profiles for tacrolimus and MPA were prospectively collected from 43 kidney transplant recipients: 27 Aboriginal and 16 Caucasian. Apparent clearance (CL/F) and distribution volume (V/F) for each individual were derived from concentration‐time profiles combined with population pharmacokinetic priors, with subsequent assessment for between‐group difference in pharmacokinetics. In addition, population pharmacokinetic models were developed using the prospective dataset supplemented by previously developed structural models for tacrolimus and MPA. The change in NONMEM objective function was used to assess improvement in goodness of model fit. Results: No differences were found between Aboriginal and Caucasian groups or empirical Bayes estimates, for CL/F or V/F of MPA or tacrolimus. However, a higher prevalence of CYP3A5 expressers (26% compared with 0%) and wider between‐subject variability in tacrolimus CL/F (SD = 5.00 compared with 3.25 L/h/70 kg) were observed in the Aboriginal group, though these differences failed to reach statistical significance ( p  = .07 and p  = .08). Conclusion: There were no differences in typical tacrolimus or MPA pharmacokinetics between Aboriginal and Caucasian kidney transplant recipients. This means that Bayesian dosing tools developed to optimise tacrolimus and MPA dosing in Caucasian recipients may be applied to Aboriginal recipients. In turn, this may improve drug exposure and thereby transplant outcomes in this group. Aboriginal recipients appeared to have greater between‐subject variability in tacrolimus CL/F and a higher prevalence of CYP3A5 expressers, attributes that have been linked with inferior outcomes. Summary at a glance: This prospective observational study examined for differences in tacrolimus and mycophenolic acid pharmacokinetics between Aboriginal and Caucasian Australian kidney transplant recipients. No differences were found, arguing against differential drug exposure as a contributor to the poorer transplant outcomes experienced by Aboriginal Australians.